ARTI PENTING DAN KARAKTERISTIK PRINSIP AKUNTANSI - Evaf Maulina (JURNAL MITRA MANAJEMEN, 2019)
Accounting principle is a guidance in summarizing and revealing the financial information. This financial information is useful for the internal and external as practical and relevant to the need of stakeholders. The stakeholders can interpretate and apply the principle well if they understand the accounting principle’s characteristics.